St. Augustinegrass for Florida Lawns - Laurie E. Trenholm; John L. Cisar; J. Bryan Unruh (EDIS)
St. Augustinegrass is widely adapted to the warm, humid (subtropical) regions of the world. It is the most commonly used lawn grass throughout the state of Florida and can grow satisfactorily in a wide variety of soils. This revised 11-page fact sheet discusses the advantages and disadvantages of this turfgrass variety, cultivars available for lawn use in Florida, establishment, maintenance, pest management, and other problems. Written by L. E. Trenholm, J. L. Cisar, and J. B. Unruh and published by the UF Department of Environmental Horticulture, April 2011.